2022
DOI: 10.1089/mdr.2021.0172
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Molecular Characterization of Gene Cassettes from Class 1 Integrons inEscherichia coliStrains

Abstract: To investigate the antimicrobial resistance and molecular characterization of gene cassettes from class 1 integrons in Escherichia coli strains isolated from hospitalized patients. Bacterial identification was conducted using the Vitek-2 Compact system, and antimicrobial susceptibility analysis was performed using the Kirby-Bauer method. Class 1 integrons, integrase genes, the variable regions of integrons and promoters from the isolated E. coli were screened by po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…In accordance with other studies, the class 1 integron was present in isolates, together with the CTX-M-15 genes and was found to be associated with genes encoding resistance to aminoglycosides (aadA gene cassettes) and/or trimethoprim (dfrA gene cassettes) [23,24]. Gene cassettes with sulphonamides (sul1) and quaternary ammonium compounds (qacE) genes) were also found on class 1 integrons that were closely associated with the chromium (chrA) resistance gene.…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with other studies, the class 1 integron was present in isolates, together with the CTX-M-15 genes and was found to be associated with genes encoding resistance to aminoglycosides (aadA gene cassettes) and/or trimethoprim (dfrA gene cassettes) [23,24]. Gene cassettes with sulphonamides (sul1) and quaternary ammonium compounds (qacE) genes) were also found on class 1 integrons that were closely associated with the chromium (chrA) resistance gene.…”
Section: Discussionsupporting
confidence: 88%
“… a DrfA17, DfrA5, DfrA12, DfrA7 encode dihydrofolate reductase conferring resistance to trimethoprim; AadA2, AadA5 encode aminoglycoside adenyltransferase conferring resistance to spectinomycin/streptomycin [ 9 , 10 ] …”
Section: Resultsmentioning
confidence: 99%
“…24 However, majority of the isolates (79.2%) were positive for NDM-1, followed by OXA-23, OXA-48, and VIM within the integron-positive population. The dominance of NDM-1 is not surprising, given that it is the most common carbapenemase gene that is found in E. coli [24][25][26][27] and; NDM-1 is particularly associated with class 1 integrons gene cassette and IncM plasmids which help them to mobilize. 34 So the co-occurrence on NDM-1 with intI1 as well as with other OXA variants is concerning as they can transfer the antibiotic resistant trait by moving between species.…”
Section: Discussionmentioning
confidence: 99%
“…And, several similar studies done in China reported similar higher antibiotic resistance in integron-positive populations. For instance, in 2022 a study 26 on clinical E. coli isolates revealed a higher resistance to Ampicillin (93%), Ciprofloxacin (80%) and Cotrimoxazole (76%). Likewise, clinical E. coli ST131 have been reported to show higher resistance to Cotrimoxazole (95%), Cefotaxime (68%), Ciprofloxacin (68%), Levofloxacin (68%) within integron-positive population 6 .…”
Section: Discussionmentioning
confidence: 99%